Development of commodity exchange in Croatia - Šicel, Mladen (Applied Studies in Agribusiness and Commerce, 2009)
Purpose of this thesis work is to show relevance and necessarity for existing of commodity exchange and it’s influence to the economy of Croatia. Because eastern part of Croatia, region called Slavonia is mostly agricultural oriented, it is of essential relevance to establish and make operate of first commodity exchange in Croatia. Widely in the past, while Croatia was part of Austrian – Hungarian kingdom, first commodity exchange in Europe that was established in 1853. in Budapest, practically was domestic commodity exchange for Croatian business subjects, and they were able to use benefits it brought. Me personally, and a lot of other business people and business society in Croatia belive that time to reasteblish commodity exchange has come. In this thesis, I will give a deeper look in to commodity exchange, describe acctual situation in Croatia, show posibillities that commodity exchange brings, how it works and what has to be done to implement commodity exchange and benefits it will bring to Croatian economy.